Characterization and thermal properties of chitosan/agar blends hydrogel membranes / Faiezah Hashim, Nor Hafizah Che Ismail and Mohd Lias Kamal - Che Ismail, Nor Hafizah; Kamal, Mohd Lias (Research Management Institute (RMI), 2011)
Continuous awareness of ecological problem has led to a paradigm shift on the use of biodegradable materials, especially from renewable agriculture feedstock and marine food processing industry wastes. Developments in the field of biomaterials have lead to significant advancements in the extraction of chitosan from local sources. Chitosan has been found in applications for biomedicine (wound dressings), tissue engineering (artificial skin), bone tissue engineering and one of the promising materials for preparing hydrophilic membranes and it has been widely studied. Most of the chitosan membranes so far have been fabricated using commercial chitosan. Nowadays, the main sources of chitosan are crab and shrimp shell. As the combination of properties of chitosan such as water binding capacity, fat binding capacity, bioactivity, biodegrability, and antifungal activity, chitosan and its modified analogs have shown many applications in medicine, cosmetics, agriculture, biochemical separation systems, tissue engineering, biomaterials and drug controlled release systems. However, chitosan also has some drawbacks, it being soluble in aqueous medium only in the presence of small amount of acid. Its mechanical properties have also proved to be unsuitable in some biomedical applications. In order to eliminate the disadvantageous, it can be modified by physical blending or/and chemical modification by grafting, interpenetrating polymer networks and crosslinking method. In this study, an attempt has been made to blend chitosan with other gelling material which is agar. Biopolymer from agar (polysaccharide) has received particular attention due to their natural origin, low cost and good compatibility. Since agar have good compatibility with most other polysaccharides and with proteins in near neutral conditions, blends of agar with chitosan may lead to the enhancement of the physical properties of chitosan membrane